Integrating the Concept of Qur’anic Geography into Sustainable Development Strategies: A Thematic Analysis of Food Security - Ery Sunandar (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2026)
Food security in Indonesia is strained by the degradation of 8.2 million hectares of agricultural land and a declining farmer regeneration rate. This study analyzes the intersection between geographic spatial instruments and Qur'anic thematic principles to formulate a more measurable sustainable development framework. Using a qualitative-interdisciplinary method, this research synthesizes spatial-ecological data with tafsir maudhu’i focused on resource management verses. The results establish a